The Effect of Endurance Training Method and Vo2max Ability on Fatigue Time in Women's Futsal Universitas Teknokrat Indonesia - Cahyo Pratomo; Sri Sumartiningsih; Agus Raharjo (JUARA : Jurnal Olahraga, 2023)
This study aims to overcome the problems that occur in the puri futsal UKM of the Indonesian Technocrat University which experiences problems in low fatigue time. The purpose of this research is to provide farlek training methods and interval training that are expected to increase the fatigue time of futsal puti SME players. The research method used in this study is an experimental method with a factorial design, there are three groups in this study including the fartlek group, interval training group, and control group with a total of 30 samples and a total of 16 training meetings. This study focuses on the time of fatigue. From the results of this study, it was found that the interval training method had a better influence than fartlek and control classes.